STRATEGI PEMASARAN PONDOK PESANTREN (NU) AL-FATAH - Muslihat, Aat (Addabani: Interdisciplinary Journal of Islamic Education, 2024)
Al-Fatah is a traditional Islamic education (Islamic boarding school) based on a Salafi approach. In the research process, this article focuses on the problems that have been formulated related to social marketing and marketing strategies implemented by Al-Fatah Islamic Boarding School. This study aims to 1) identify educational marketing strategies at Al-Fatah Islamic Boarding School and 2) analyze social marketing to improve educational strategies in a competitive era. This research method uses qualitative research developed by descriptive analysis. This study found that educational marketing carried out by Al-Fatah consisted of ten (10) types: Kyai, publications (Mass Media, Banners, Brochures, Calendars), social media (Facebook, Website, WhatsApp), community participation, and alumni. Seeing the development of education in a competitive era, pesantren leaders have responded to these conditions. For example, he established a well-established formal education (RA, MTs, and MA) and several support activities for students, including Student Organizations, Scouts, Student Health Organizations, Sports, Music, Marawis, Computer Courses, Muhadharah, and Qira'ah Al-Qur'an.